ISLAMIC LAW ANALYSIS OF THE ROLE OF THE HEFORSHE CAMPAIGN IN PROTECTING WOMEN IN THE PALEMBANG COMMUNITY - Riska, Mira Novita; Nurnazli, Nurnazli; Zuhraini, Zuhraini (Universitas Islam Negeri Raden Intan Lampung, 2024)
The title of the article is HeForShe's Role in Palembang Society. She invites men of all ages as equal partners in building a women's rights movement and implementing a shared vision of gender equality that benefits all humanity. The campaign sought to actively involve men and boys in a movement initially conceived as